A 0.052 mm2, <0.4% THD, Sinusoidal Current Generator for Bio-Impedance Measurement Using a Recursive Digital Oscillator and Current-Domain FIR Filter - Hong, Seok Ki; Jee, Dong Woo (IEEE Transactions on Circuits and Systems II: Express Briefs, 2019)
This brief presents a low-power, low-area and low total harmonic distortion (THD) sinusoidal current stimulator circuit for bio-impedance measurement. Proposed current generator includes recursive digital oscillator for sine wave generation and delta-sigma modulated 1 bit current source with embedded finite impulse response filter for high resolution digital-to-current conversion. The proposed circuit implemented in 0.18-μ m CMOS process occupies 0.052 mm2, and consumes 55.6 μ W for 20 kHz, 40 μ Ap-p, 0.17% THD sine current generation.
Keywords: Bio-impedance; Delta sigma modulator; Digital oscillators; Low area; Low Power; Sine wave generator; Total harmonic distortion (THD); bio-impedance; delta-sigma modulator; FIR filter; low area; low power; recursive digital oscillator; Sine wave generator; total harmonic distortion